From milk by-products to milk ingredients : upgrading the cycle - Boer, Ruud de (John Wiley & Sons, 2014)
Milk is a complex substance, and a variety of constituents can be extracted from it for use as ingredients in other foods. The main ingredients from milk are milk fat, cheese and serum, but this range is continually expanding as food companies, dairies and dairy scientists seek to utilize as many raw materials and by-products as possible, to reduce waste, maximize efficiency, and increase productivity. Ingredients from Milk is a concise, fresh approach to ingredients derived from milk, containing guidance and new techniques for dairy industry professionals and scientists.<br